Contractual Private Disclosures in Supply Chains and Managerial Learning from Financial Markets - Pandey, Vivek (The Accounting Review, 2026)
ABSTRACT I examine whether contracts that require customers to privately share with suppliers forecasts of their future demand for the supplier’s products (“demand forecast contracts,” or “DF contracts”) affect the supplier’s reliance on an alternative information source—stock prices—when making investment decisions. If suppliers find these forecasts a more direct signal of future demand than stock prices, they may reduce their reliance on stock prices to guide investments. Using hand-collected data, I find that suppliers’ investments become significantly less sensitive to stock prices after entering a DF contract for the first time. This effect is stronger when forecasts are more credible, demand more uncertain, and investments more irreversible. Supplier performance, measured by return on assets and cash flow from operations, improves post-DF. Overall, these findings suggest that when a relatively direct information source about future demand becomes available, managers reduce their reliance on stock prices in making real decisions. Data Availability: Data are available from public sources cited in the text. JEL Classifications: G10; G30; G31; L14; M40; M41.